Judaean Ethnicity and Christ-Following Voluntarism? A Reply to Steve Mason and Philip Esler - Horrell, David G. 1963- (2019)
In NTS 63 (2017), Steve Mason and Philip Esler responded to an earlier article of mine by setting out their grounds for a categorical distinction between Judaean ethnic' identity and Christ-following voluntary association and by rejecting the idea that drawing this contrast could reflect or legitimate modern notions of implicit Christian superiority. In this reply, intended to clarify the issues at stake and the grounds for disagreement, questions are first raised about various aspects of the approach to ethnicity that Mason and Esler adopt, illustrating the main points with brief examples from relevant texts and contemporary scholarship. Specifically, I consider the value of multiple rather than singular categorisations, the idea that ethnicity should be seen as multiple, fluid and hybrid in character, the relationship between ethnicity and religion, and the contrast between real and fictive kinship. Finally, I return to the issue of the ways in which scholarship may reflect its contexts of production and the need to probe this critically, offering specific illustrations of the reasons for my claims. Whether my particular suggestions concerning the implications of the dichotomy between Judaean/Jewish ethnicity and trans-ethnic' Christian identity are right or wrong, I argue for the importance of critical reflection on the impact of contemporary location on historical reconstruction.
Keywords: Judaean/Jewish identity; contemporary ideologies; Early Christian Identity; ethnic fluidity; ethnic hybridity; Ethnicity; Kinship; Religion